The changes in maximal oxygen uptake (V̊O2MAX) induced by physical exertion during an Antarctic expedition depend on the initial V̊O2MAX of the individuals: a case study of the Brazilian expedition - Michele M. Moraes; Thiago T. Mendes; Ygor A.T. Martins; Cristian N. Espinosa; Chams B. Maluf; Danusa D. Soares; Samuel P. Wanner; Rosa M. E. Arantes (International Journal of Circumpolar Health, 2018)
Antarctic climate is challenging, since the cold, wind and sensory monotony are stressful stimuli to individuals. Moreover, camp activities and heavy clothes may contribute to increase physiological strain. Thus, we aimed to characterise the physiological demand of a 24-day period in the Antarctic field and then to evaluate the effect of this expedition on the aerobic fitness in individuals with heterogeneous initial aerobic fitness (as determined by estimating maximum oxygen consumption – V̊O2MAX). Before and after the 24-day period in Antarctica, 7 researchers and 2 mountaineers were subjected to incremental tests to estimate their V̊O2MAX. Field effort was characterised by measuring heart rate (HR). During the field trips, their HR remained 33.4% of the recording time between 50–60% HRMAX, 22.3% between 60–70% HRMAX, and only 1.4% between 80 and 90% HRMAX. The changes in estimated V̊O2MAX during the expedition depended on the pre-expedition aerobic fitness. The post-expedition V̊O2MAX increased by 5.9% and decreased by 14.3%in individuals with lower (researchers) and higher (mountaineers) initial V̊O2MAX, respectively. We concluded that physical effort in the Antarctic field is characterised as predominantly of low- to moderate-intensity. This effort represented an effective training load for individuals with lower initial V̊O2MAX, but not for those with higher V̊O2MAX.